Implementation of government housing delivery programme in the Gravellotte area of Ba-Phalaborwa Municipality, Limpopo - Mnisi-Mudunungu, Gloria Dzunisani (University of Limpopo (Turfloop Campus), 2011)
The study aims at investigating the extent to which the Housing Delivery Programme of Government is addressing the backlog in housing provision. In the other hand if Government is not addressing the backlog in housing, it should be established as to what are the casual factors to the failure. The study randomly selected participants from Gravellotte to answer questions in connection with the two housing projects in Gravellotte, as well as officials of the Department of Local Government & Housing and the municipality of Ba-Phalaborwa. Primary data from participants and secondary data from books and journals were used. Qualitative method was more suitable for the study. It has been found that government is continuously providing houses, but the pace does not address the backlog in a quicker way as expected by the community and the quality of houses remain an issue that needs serious attention.
Thesis (MPA) --University of Limpopo, 2011
Keywords: Housing delivery; Housing project; 353.55; Housing -- South Africa -- Limpopo; Housing policies -- South Africa -- Limpopo